Home-based digital leisure: Doing the same leisure activities, but digital - López-Sintas, Jordi (Cogent social sciences, 2017)
The introduction of the information and communication technologies in the home has transformed free-time leisure activities. Adopting a constructivist and interpretive perspective, we analysed 30 individual narratives in order to describe how digital technologies have transformed home-based leisure activities. The findings show that the changes brought about are qualitatively different from those produced by previous technological devices. The digital technologies have not only increased exposure to different experiences, they also allow people to control those experiences. The consumption of experiences is no longer homogeneous among household members and individuals now have greater freedom regarding their choice of home-based leisure activities. The findings of this study, suggest that digital leisure has transformed home-based leisure, can be used to understand home-based leisure technologies. Further studies are required to explore home-based digital leisure in other areas of people’s lives as digital technologies, devices and applications evolve.